Formation and evolution of executive power (Journal of actual problems of jurisprudence, 2019)
The article con fi rms the historical law of development of the institution of public administration, in which without bias changingsocio-legal and political appointment of the state, its institutions and agencies already have a high dynamics of the institutions of publicadministration. In this regard, the author emphasizes that the general historical analysis is important from the viewpoint of understanding the natural history of the concept of development of the institutions of power and control, providing the necessary rational andnatural phenomenon in order to include them in the improvement and implementation of democratic governance models in the legalsystem of Kyrgyzstan.